PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN BAWANG MERAH (ALLIUM CEPA L.) MENGGUNAKAN HIDROPONIK SISTEM WICK - Masaning Previanti, Melda; Tyastirin, Esti (Universitas Cokroaminoto Palopo, 2025)
Onion are one of the many types of shallots that exist in the world. Shallots are a member of the Allium genus which is usually used as a cooking spice. Demand for shallots will continue to increase along with people's needs that continue to increase. Hydroponics is a method of growing crops without using soil, usually using cocpeat, husks and sand as a substitute for soil. One hydroponic model that is easy to implement is the wick system method, where in this system the plants absorb water through the wick. The parameters observed were plant height, root length and number of tubers. The results of the research showed that the planting medium did not have a real influence on plant height and number of tubers, but on root length the planting medium had a real influence. The best planting medium for growing tall shallots is husk media: cocopeat (1:1) with the highest score of 27.90. Meanwhile, the root length and number of shallot bulbs were highest in the husk: sand (1:1) media with values of 16.00 and 6.22.